Analysis of parasitic effects in carrier signal injection methods for sensorless control of PM synchronous machines. Issue 2 (2nd January 2018) - Xu, Peilin; Zhu, Z.Q.
Abstract : This study presents the parasitic effects on different carrier signal injection methods with alternative sensing signals for the sensorless control of permanent magnet synchronous machines (PMSMs). The different carrier injection methods are the rotating injection in the stationary reference frame with carrier current sensing and with zero‐sequence carrier voltage sensing, the pulsating injection in the estimated synchronous reference frame with carrier current sensing, and pulsating injection in the anti‐rotating reference frame with zero‐sequence carrier voltage sensing, respectively. The parasitic effects, e.g. the magnetic saturation, inverter non‐linearity, iron and PM losses, torque ripple etc. will be fully analysed and compared for these different injection methods. All the theoretical analyses are validated by either finite‐element analyses or experiments on a laboratory PM machine.